GE_GERICHTE C/19823/2014 vom 16. Februar 2015 - GE Cour de justice (2015)
BAIL À LOYER; ÉVACUATION(EN GÉNÉRAL); CAS CLAIR; MOTIVATION DE LA DEMANDE; CONDITION DE RECEVABILITÉ | CPC.321.2; CPC.257.1; CO.257d.1; CPC.236.3